Programming the Web: An Introduction - Sosinsky Barrie (McGraw -Hill, 2004)
PROGRAMMING THE WEB by Barrie Sosinsky is designed for the first course in a web-programming curriculum. Students are first exposed to the fundamentals of web programming used in the majority of the languages covered. The text then delves into the specifics of HTML, XML, Java, JavaScript, ASP, and Perl /CGI. This book ultimately lays the basic foundation for web programming.